1982
DOI: 10.1128/aem.44.5.1059-1063.1982
|View full text |Cite
|
Sign up to set email alerts
|

Plants as Sources of Airborne Bacteria, Including Ice Nucleation-Active Bacteria

Abstract: Vertical wind shear and concentration gradients of viable, airborne bacteria were used to calculate the upward flux of viable cells above bare soil and canopies of several crops. Concentrations at soil or canopy height varied from 46 colonyforming units per m3 over young corn and wet soil to 663 colony-forming units per

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(149 citation statements)
references
References 29 publications
9
131
1
5
Order By: Relevance
“…Bacteria.-Our findings agree with previous studies of aerosolized microbes that have reported dominance of Actinobacteria, Cyanobacteria, Firmicutes, Bacteroidetes, and Proteobacteria, particularly Alphaproteobateria and Gammaproteobacteria (Lindemann et al 1982, Bowers et al 2013, Striluk et al 2016. These findings are also in general agreement with the limited number of studies that have examined the microbes in clouds and precipitation (Va€ ıtilingom et al 2012, Santl-Temkiv et al 2015, Amato et al 2017a.…”
Section: Taxonomic Composition Of Sequence Librariessupporting
confidence: 92%
“…Bacteria.-Our findings agree with previous studies of aerosolized microbes that have reported dominance of Actinobacteria, Cyanobacteria, Firmicutes, Bacteroidetes, and Proteobacteria, particularly Alphaproteobateria and Gammaproteobacteria (Lindemann et al 1982, Bowers et al 2013, Striluk et al 2016. These findings are also in general agreement with the limited number of studies that have examined the microbes in clouds and precipitation (Va€ ıtilingom et al 2012, Santl-Temkiv et al 2015, Amato et al 2017a.…”
Section: Taxonomic Composition Of Sequence Librariessupporting
confidence: 92%
“…Across pathovars, it infects a wide variety of species including tomato, kiwifruit, and soybean (Sarkar and Guttman 2004). After arriving on a suitable host by wind or rain-mediated dispersal, it begins as an epiphyte on leaf surfaces (Lindemann et al 1982;Constantinidou et al 1990). Once reaching a sufficiently high density as determined via quorum sensing, the bacterium enters the apoplast (internal intercellular space) of the leaf through stomata or wounds (Quiñones et al 2005;Misas-Villamil et al 2013).…”
Section: Study Systemmentioning
confidence: 99%
“…However, there has not been a formal demonstration of this phenomenon, mostly due to the paucity of studies of microbial flux in the atmosphere (Morris et al, 2013a). Nevertheless, in one of the few studies of microbial flux, upward flux over crops was the highest over the crops having the most dense microbial populations on their leaves (Lindemann et al, 1982). Overall, plant quality affects the abundance of biological ice nuclei in the atmosphere, with the greatest concentrations being observed over agricultural land than over suburban land or forests (Bowers et al, 2011).…”
Section: Componentmentioning
confidence: 99%
“…Emission rates and average atmospheric concentrations for fungal spores are estimated to be on the same order of magnitude (Elbert et al, 2007;Sesartic & Dallafior, 2011;Despres et al, 2012;Huffman et al, 2012;Santl-Temkiv et al, 2013). Vegetation is implicated as the main source of air-borne microorganisms, and more so than bare soil (Lindemann et al, 1982;Lighthart, 1997;Burrows et al, 2009). In a study of the composition of hailstones, the culturable bacterial community was skewed toward groups of bacteria most common on plants, whereas their dissolved organic matter content was mainly from soils (vs. plants) ( Santl-Temkiv et al, 2013).…”
Section: Landscapes Aerosols and Phenomena Coherent With Bioprecipitmentioning
confidence: 99%
See 1 more Smart Citation